Health advice on alcohol consumption in pregnant women in Seville (Spain) - Ramón Mendoza; Elena Morales-Marente; M. Soledad Palacios; Carmen Rodríguez-Reinado; Isabel Corrales-Gutiérrez; Óscar García-Algar (Elsevier, 2020)
Objective: To analyse to what extent pregnant women remembered having received health advice regarding alcohol consumption during pregnancy, what the message they perceived was and whether there is social inequality in this regard. Method: A cross-sectional descriptive study was performed with a sample of 426 pregnant women (in their 20th week of pregnancy) receiving care in the outpatient clinics of a university hospital in a southern Spanish city (Seville). The data were collected through face-to-face structured interviews carried out by trained health professionals. Results: 43% of the interviewed women stated that they had not received any health advice in this regard. Only 43.5% of the sample remembered having received the correct message (not to consume any alcohol at all during pregnancy) from their midwife, 25% from their obstetrician and 20.3% from their general practitioner. The women with a low educational level were those who least declared having received health advice on the issue. Conclusion: The recommended health advice to avoid alcohol consumption during pregnancy does not effectively reach a large proportion of pregnant women. Developing institutional programmes which help healthcare professionals to carry out effective preventive activities of foetal alcohol spectrum disorder is needed. Resumen: Objetivo: Analizar en qué medida las gestantes recuerdan haber recibido asesoramiento sanitario sobre el consumo de alcohol durante el embarazo, cuál es el mensaje percibido y si existe desigualdad social al respecto. Método: Se realizó un estudio transversal descriptivo con 426 mujeres en su semana 20 de embarazo en las consultas externas de un hospital universitario de Sevilla (España). Los datos se recopilaron mediante entrevistas estructuradas cara a cara realizadas por profesionales sanitarias entrenadas. Resultados: El 43% de las entrevistadas afirmaron no haber recibido consejo sanitario alguno al respecto. Solo el 43,5% dijeron que habían recibido el mensaje correcto (no beber absolutamente nada de alcohol durante el embarazo) por parte de la matrona, el 25% por el obstetra y el 20,3% por el médico de atención primaria. Las embarazadas con menor nivel educativo fueron las que menos refirieron haber recibido asesoramiento sanitario sobre el tema. Conclusión: El consejo sanitario adecuado (evitar todo consumo de alcohol durante el embarazo) no llega de manera efectiva a una amplia proporción de las gestantes. Es necesario desarrollar programas institucionales que posibiliten que los profesionales sanitarios puedan llevar a cabo con eficacia actividades preventivas de los trastornos del espectro alcohólico fetal.